Using Soils to Guide Fertilizer Recommendations for Southern Pines - Eric J. Jokela; Alan J. Long (EDIS)
Soils supporting southern pine stands in the South tend to be infertile and nutrient additions are often required to achieve optimum rates of production. This revised 12-page publication describes and classifies soils of the southeastern Coastal Plain region and specifically addresses issues of fertility, growth-limiting nutrients, and fertilizer recommendations for southern pines. Written by Eric J. Jokela and Alan J. Long, and published by the UF Department of School of Forest Resources and Conservation, June 2012.